Understorey species diversity and its effect on soil temperature and relative humidity in the Riparian Zone of Pusur River. Issue 1 (1st April 2022) - Febry Anggana, Alvian; Mujiyo
Abstract: Climate change has had a negative impact on all of life aspects. Currently, we have seen frequent occurrences of droughts, rising temperatures, floods, landslides. Therefore, mitigation and adapatation efforts are needed to reduce climate change. One of these efforts is Identify the diversity of riparian understorey plants todetermine their role in the riparian microclimate.This study aims to determine the diversity of understorey plants and their effect on temperature and soil moisture in the Riparian Pusur. It was carried out along the Pusur River, from the upstream to the downstream (administratively included in Boyolali Regency and Klaten Regency) in August 2021. A vegetation analysis method was employed. Sample was obtained from nine observation stations in which 10 plots (2 m × 2 m in size) were established in each station, at elevation 100-800 m asl. This study identifies 9364 individuals that belong to 74 species and 35 families. The lower Upstream has the highest species diversity (30 species), while the mid Downstream has the lowest (14 species). Based on the measurement of the soil temperature, the lowest temperature is in the upper Upstream of 27°C, while the highest is in the lower Downstream of 33°C. The average relative humidity ranges from 39 to 60%. This study concludes that the maximum H' is identified at soil temperature of 27-28.8°C and relative humidity of 59-61% with the species diversity of riparian understorey ranges from 2.9 to 3.08.